IMPLEMENTASI SINGLE MINUTE EXCHANGE OF DIES (SMED) UNTUK PERBAIKAN PROSES BRAND CHANGEOVER MESIN FOCKE DAN PROTOS - Ade Astuti Widi Rahayu (Lembaga Penelitian dan Pengabdian pada Masyarakat, Universitas Buana Perjuangan Karawang, 2020)
The setup process at the time of brand change (Brand Changeover) that often occurs in machines has an impact on small performance values ​​and the potential for delays in the distribution schedule so that in these conditions stock outs occur in the market and cannot meet consumer needs according to the schedule that has been set. So that it is necessary to pay attention and observe the brand transfer activities on the maker and packer machines so that these activities are more efficient. From the results of the analysis, it is known that the brand change process that occurs in the SPM area takes a long time. With the process of separating external and internal activities with the SMED method, and paralleling internal activities in a process, it is expected to be able to improve production performance. The average time required for the protos machine to make a brand change is 85,078 minutes and the Focke engine is 179,105 minutes. The SMED method and separating external and internal activities can reduce 27.834% Brand Change time for Protos machines and 42.243% Brand Change time for Focke machines. From the implementation of this method for 7 weeks, it can be seen that the reduction in Brand change time can increase the machine's Link Up uptime performance by 6.48%.